Synthesis, crystal structure, stability studies, DNA/albumin interactions, and antimicrobial activities of two Cu(II) complexes with amino acids and 5-nitro-1, 10-phenanthroline. Issue 3 (1st February 2017) - Inci, Duygu; Aydin, Rahmiye; Sevgi, Tuba; Zorlu, Yunus; Demirkan, Elif
Abstract: One-dimensional (1-D) coordination polymer and mononuclear copper(II) complexes, ([Cu(nphen)(asn)]ClO4 )n (1 ) and [Cu(nphen)(gln)(H2 O)]ClO4 ·H2 O (2 ) (nphen = 5-nitro-110-phenanthroline, asn = asparagine, gln = glutamine), have been synthesized and characterized by IR spectroscopy, ESI-MS, CHN analysis, and single-crystal X-ray diffraction. These binary and ternary complexes of copper(II) with nphen, asn, and gln have been investigated using potentiometric methods in 0.1 M KCl aqueous ionic media at 298.2 K. The protonation constants of the ligands and the stability constants of1 and2 have been calculated from the potentiometric data using the "BEST" software package. The potentiometric results have been analyzed using the "SPE" software package, and the distribution curves for the copper-containing species have been determined for the ternary systems. The CT-DNA-binding properties of these complexes have been investigated by thermal denaturation measurements and both absorption and emission spectroscopy. Further, the interaction of these complexes with bovine serum albumin (BSA) and human serum albumin (HSA) has been investigated using absorption and emission spectroscopy. The thermodynamic parameters, free energy change (ΔG), enthalpy change (ΔH), and entropy change (ΔS) were calculated by the van't Hoff equation and discussed. The distances between the serum albumins and1 and2 have been obtained according to fluorescence resonance energy transfer (FRET). Conformational changes of serum albumins have been observed from synchronous fluorescence technique. The antimicrobial activity of the complexes has also been tested on some bacteria. The effect of different amino acids on the copper(II) complexes are discussed. Abstract :